An English language training needs analysis for civil servants in an Indonesian industrial city - Wigati, Fikri Asih; Dafitri, Fela; Hakim, Putri Kamalia; Pujiawati, Nia; Rahma, Fika Natasya (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study investigates the English language training requirements of civil servants at the Personnel and Human Resource Development Agency in an Indonesian industrial city. A systematic needs analysis approach used to examine current proficiency levels, identify specific skill gaps, and determine preferred learning methodologies among 50 government employees in an industrial area. The research used a mixed-methods design integrating demographic surveys, self-assessment questionnaires, and analysis of workplace context. The study results revealed significant proficiency gaps, especially in oral communication skills, with 78% of participants rating their speaking abilities as poor or moderate. The priority training areas included technical terminology in public administration, professional communication, and service for international visitors especially from industry. The results show that instead of general English instruction, civil servants need specialized English for Specific Purposes (ESP) training. In order to improve institutional capacity for international engagement, the study offers evidence-based recommendations for curriculum design, scheduling preferences, and assessment frameworks.